“Close your eyes. Picture a character. . .”: A Route to Imagery and Creativity - Németh, Lenke (Hungarian Journal of English and American Studies, 2020)
Book review: García-Romero, Anne. The Fornes Frame: Contemporary Latina Playwrights and the Legacy of Maria Irene Fornes. Tucson: U of Arizona P, 2016. xiii + 240 pages. ISBN 978-0816531448. Pbk. 24.95.